Optimization of Processing Conditions of Alkali Treated Cottonii (ATC) from Sap-free Eucheuma cottonii - Fateha, Fateha; Wibowo, Singgih; Santoso, Joko; Agusman, Agusman; Uju, Uju (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2019)
Alkali treated cottonii (ATC) is a derivative product of Eucheuma cottoniithat is treated with alkali. This study used raw material of sap-free seaweed for ATC processing. Sap-free seaweed is a seaweed which thallus has been extracted with liquid known as sap. The use of sap-free seaweed as an ATC product is constrained by its low quality, so an effort to improve its quality is needed. Therefore the obejcetive of this Research was to get the optimal conditions of ATC processing. Experimental data were designed and analyzed using Response Surface MethodologyCentral Composite Design (RSM-CCD) using Design Expert 10.0.7Â® program. The optimization of ATC processing involved three components that were considered influential, namely KOH concentration, temperature, and processing time. Recommendation for optimal conditions issued by RSM-CCD on ATC processing from sap-free seawee d were 6 % KOH concentration at 75 oC for 120 minutes (93.1% desirability). The results of the response analysis showed a yield of 39.47% and a gel strength of 595.32 g/cm2. As a research control, the recommendation of RSMCCD used in ATC processing from nonsap-free seaweed was obtained yield of 36.81% and gel strength of 574.44 g/cm 2. ATC from sap-free seaweed has higher yield and gel strength than that from nonsap-free seaweed. Thismight be due to the sap-free seaweed was obtained using the proper sap extraction process and ATC processingunder optimal conditions, so that the quality of seaweed was better maintained.